2015
DOI: 10.1037/cns0000042
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and functions of involuntary and voluntary autobiographical memories across the day.

Abstract: Berntsen, D. (2015). The frequency and functions of involuntary and voluntary autobiographical memories across the day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 52 publications
7
67
0
Order By: Relevance
“…It seems that the possibilities and opportunities here are massive, and as indicated at the outset, semanticautobiographical priming could potentially account for a great deal of everyday involuntary autobiographical remembering. For example, a number of studies and writers have suggested that a portion of involuntary memories may be functional (i.e., serve some purpose), whereas another portion of them may be non-functional or random (see, Berntsen, 2009;Mace, 2017;Mace & Atkinson, 2009;Rasmussen & Berntsen, 2009;Rasmussen et al, 2015). Perhaps semantic-autobiographical priming accounts for a good proportion of the random component of involuntary memories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the possibilities and opportunities here are massive, and as indicated at the outset, semanticautobiographical priming could potentially account for a great deal of everyday involuntary autobiographical remembering. For example, a number of studies and writers have suggested that a portion of involuntary memories may be functional (i.e., serve some purpose), whereas another portion of them may be non-functional or random (see, Berntsen, 2009;Mace, 2017;Mace & Atkinson, 2009;Rasmussen & Berntsen, 2009;Rasmussen et al, 2015). Perhaps semantic-autobiographical priming accounts for a good proportion of the random component of involuntary memories.…”
Section: Discussionmentioning
confidence: 99%
“…Priming involuntary autobiographical memories Spontaneous recollection of the past appears to be common in everyday life (e.g., Ball & Little, 2006;Berntsen, 1996Berntsen, , 1998Mace, 2004Mace, , 2005Schlagman & Kvavilashvili, 2008; see reviews in Berntsen, 2009;Mace, 2007bMace, , 2010a. While early studies had placed estimates of the occurrence of involuntary memories to be between three and five per day (Berntsen, 1996(Berntsen, , 1998, more recent studies have suggested that their occurrence may be around 20 per day, perhaps outstripping voluntary autobiographical memory occurrence (Rasmussen & Berntsen, 2011;Rasmussen, Ramsgaard, & Berntsen, 2015). By definition, involuntary autobiographical memories are random in the sense that one does not intend to remember the past event.…”
Section: Priming and Activation In Autobiographical Memorymentioning
confidence: 99%
“…Involuntary autobiographical memories are at least as frequent in daily life as autobiographical memories that are deliberately (voluntarily) retrieved (e.g., Rasmussen & Berntsen, 2011; Rasmussen, Ramsgaard & Berntsen, in press; Rubin & Berntsen, 2009), although measures of their frequencies tend to vary with the amount of effort imposed by the recording task (Rasmussen et al, in press). Importantly, substantial individual variability is seen, both when involuntary memories are recorded in real time in diary studies and retrospectively in survey studies (see Rasmussen et al, in press, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, substantial individual variability is seen, both when involuntary memories are recorded in real time in diary studies and retrospectively in survey studies (see Rasmussen et al, in press, for a review). Only few studies have analyzed dispositional and demographic correlates of this variability.…”
Section: Introductionmentioning
confidence: 99%
“…Interest on studies related to antecedents of future thoughts has been on the increase in the existing body of literature (Hall and Berntsen, 2008;48-57;Rubin & Berntsen, 2009;591-614;Eryilmaz, 2011;Rasmussen & Berntsen, 2011;1842-1846Finnbogadottir and Berntsen, 2013;625-640;Rasmussen, Ramsgaard, Berntsen, 2015;185-205). Some of these studies have examined the relation between the frequency of voluntary or involuntary autobiographical memories and future thoughts among undergraduate and graduate students.…”
Section: Future Thoughtsmentioning
confidence: 99%